ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG GALAXY (Studi Kasus Pada Mahasiswa FISIPOL Di Universitas Mulawarman Samarinda) - Thycha Ancila; Suharno Suharno; Muhammad Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study to determine the effect of brands on purchase decisions phone Samsung galaxy. This research is a quantitative survey approach. The sampling technique used purposive sample tekni which researchers select members of the population who incidentally met with investigators and is considered to provide the necessary information.               The independent variables consist of Brand Awareness (X1), Trademark Association (X2), Perceived Quality (X3), while the dependent variable is the purchase decision (Y), Methods Data were analyzed using multiple linear regression with F test and t test.               The results showed that Brand Awareness (X1), Trademark Association (X2), Perceived Quality (X3) simultaneously significantly influence the purchase decision Mobile Samsung galaxy on FISIPOL student at the University of Mulawarman Samarinda.Keywords: Brand Awareness, Trademark Association, Perceived Quality and purchase decision